Organizational Citizenship Behavior, Reward, Punishment To Improve Employee Performance - Sutianingsih Sutianingsih; Selvi Mega Agustina (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Human resources are important in an organization because the success of an organization depends largely on the quality and performance of the individuals in the organization. This study analyzes team member performance influenced by organizational citizenship behavior, reward, and punishment. The population of all employees of the Cahaya Sentosa Cooperative in Purwodadi is 101 people. The sampling technique uses saturated sampling techniques. Research instruments with questionnaires that have been tested for validity and reliability. Analysis with multiple linear regression, data processed with SPSS 24.0 for windows program. In conclusion, organizational citizenship behavior does not affect team member performance; reward and punishment variables positively and significantly affect staff performance. Punishment has the greatest (dominant) influence on team member performance. Keywords: Organizational Citizenship Behavior, Reward, Punishment, Employee Performance